Answer:
( 4,3) Answer by using any method you choose such as elumination or substitution but today I would rather use elimination so multiply 3 on both sides of the first equation dont rewrite it you should have now: 9x+6Y=54 Now multiply the Bottom equation by 2 you should now have: 8x-6Y=14 the rewrite again put 9x+6Y=54 on top and 8x-6Y=14 on the bottom -6 and positive 6 is marked out now 9x+8X is then all you have to do is add 9x+8x and 14 +54 you get 17x=68 then divide x=4 then u have to substitute the X value to the equation 4x-4y=7 then y=3